Parental attitudes towards mainstreaming/inclusion of children with special educational needs in regular classrooms and schools - Glassman, Jennifer A. (My University, 2014)
This study examines parental attitudes towards mainstreaming/inclusion in South Africa, which was recently adopted as part of the new educational dispensation. The sample included parents of children in four different school types in Johannesburg, and the survey was conducted by means of a questionnaire with multiple-choice and open-ended sections. The respondents totaled 255 out of a possible 400 (64%). Statistical analyses used included factor analysis, analysis of variance and independent group t-tests. The results indicated an overall neutral or negative attitude towards mainstreaming by parents, with parents of children in special and remedial schools being more negative. Parents felt that gifted children or those with mild to moderate learning disabilities were the most suitable candidates for mainstreaming, whilst children with severe mental retardation, sensory impairments, or behavioural disorders were the least suited. Parents were concerned that teachers would not be able to cope with the demands of the mainstream classroom because of inadequate training or time. They were also concerned that classes would be too large, that children of differing abilities would not be able to cope with the academic and social demands placed on them, and that general educational standards would drop. Only 20% of parents felt that mainstreaming would be successful, and most parents were not clear about what measures could help to implement this educational approach in South Africa. The implications of these results were discussed, with a view to future research and interventions to allay parental fears about mainstreaming/inclusion
Thesis (M.Ed.)--University of the Witwatersrand, Faculty of Education, 1999.
Keywords: mainstreaming; inclusion; children with special educational needs; parental attitudes; parental concerns